Isolation of lactic acid bacteria from the digestive tract of the piglet - Sánchez Súarez, Héctor (2017)
The aim of the study was to isolate and identify native lactobacillus microorganisms from the digestive tract of piglets with the possibility of using them for the improvement of the productive performance of piglets. Samples were cultured and purified on Man, Rogosa and Sharpe (MRS) agar. Molecular identification of the bacteria was done by the sequencing the 16S rRNA gene. Four species were identified: Lactobacillus johnsonii, Lactobacillus brevis, Enterococcus hirae and Pediococcus pentosaceus.